A109 LINKING PRIMARY AND SPECIALTY CARE FOR THE MANAGEMENT OF DIGESTIVE HEALTH CONDITIONS: AN EVALUATION OF GUT LINK IMPLEMENTATION. (4th March 2021) - Stewart, M J; Heisler, C; Kohansal, A R; Patel, S; Williams, G; Williams, S; Miles, M; Zhu, J; Kulai, T; Peltekian, K; Gruchy, S E; Epstein, I; et al.
Abstract: Background: Severe restrictions on in-person encounters and endoscopic procedures for digestive care have occurred as a result of the COVID-19 pandemic. This has exacerbated pre-existing barriers in access to gastroenterology (GI) care across Nova Scotia (NS) for patients and primary healthcare providers (PHCPs). In response, a provincial PHCP-GI consultative service (GUT LINK) was implemented at a single tertiary care center with the goal of supporting PHCPs in the management of non-urgent GI referral conditions. Aims: To implement and evaluate the acceptability, feasibility, appropriateness, and early effectiveness of the GUT LINK PHCP-GI consultation service. Methods: This is an ongoing prospective observational cohort study. All referrals received through the EMR-based referral and triage management system between May and November 2020 that were deemed to be amenable to management within primary care with specialist support were returned to the PHCP with the suggestion to arrange a GUT LINK telephone consultation. GUT LINK appointments were scheduled through an administrative support telephone line with the PHCP and a GI specialist. A post-consultation e-questionnaire was distributed to PHCPs who consented to participate. Feasibility (number of and indication for referrals, PHCP participation rates), acceptability and appropriateness (satisfaction, future use, likelihood to recommend) metrics and outcomes (case resolution, re-referrals, proportion requiring endoscopic investigations) were recorded. Patient charts were reviewed to determine whether the patient ultimately required GI speciality care. Analyses were descriptive and expressed as frequencies, means (+/-SD), medians (+/-SE), and proportions (%). Results: A total of 45 GUT LINK consultations were completed between May and November 2020. Of these, 20% required GI specialist care and 80% have remained within primary care, with a median follow-up of 101 (+/-9.1) days. The indications for GUT LINK consultation included lower GI symptoms (64%), abnormal imaging or investigations (17%), and upper GI symptoms (19%). To date, 21 PHCP agreed to be contacted for the post-consultation survey and 10 have been completed. All PHCPs reported that GUT LINK consultation was easy to access, while 90% found the advice helpful and 80% reported that that it resolved the issue. Following the GUT LINK appointment, 80% felt they would not need to refer their patient to GI. Conclusions: The implementation of GUT LINK was acceptable, feasible, and improved access to specialist support for management of undifferentiated GI symptoms. Future research will focus on comprehensive stakeholder engagement in order to design, implement, and evaluate GUT LINK PHCP care pathways. Funding Agencies: CAG